FORT BRANCH, HAMILTON COUNTY, NORTH CAROLINA: RESEARCH DESIGN AND SITE MANAGEMENT PLAN - Heinrich, Keith T. (My University, 2004)
The purpose of this thesis is to produce a research design and a site management plan for Fort Branch, a National Register-listed Confederate earthwork on Rainbow Bend in Martin County, North Carolina. The thesis discusses the history of Fort Branch, starting with a history of the Civil War in eastern North Carolina, to provide a context for the fort’s construction. A specific history of the fort discusses the defenses of Rainbow Bend and their eventual evolution into what is now Fort Branch. The research design uses the historical and archaeological background to formulate site-specific archaeological questions and uses case studies of Civil War archaeology to ensure that research at Fort Branch is placed within the context of Civil War archaeology. Previous archaeology, the archaeology of fort construction, an archaeological survey of the site, the archaeology of skirmishes, the archaeology of encampment, landscape studies, and the historic cemetery are discussed in this thesis. This research is important because it will provide the Fort Branch Battlefield Commission with ways to better interpret the battlefield, enhance its mission of preservation and restoration, and provide ways that the site can be protected for future generations.